Personnel Information System Strategic Planning Using the Ward and Pepprad Method (Case Study: SMP N KARANGPUCUNG) - Farid Arifin; Dwi Mustika Kusumawardani; Fahudin Muktiwibowo (Soegijapranata Catholic University, 2023)
Information Systems (IS) now have a very necessary use for agencies in business activities. The role of SI in the business contribution of agencies that have implemented IS management in their business activities, namely the education office. Strengthened by Law Number 20 of 2003 concerning the National Education System where facilities and infrastructure are needed to support education to become more systematic and to support learning and administration in education. The education sector that uses information systems in carrying out its business is SMP Negeri 1 Karangpucung. Based on interviews conducted with Mr. Asep Ibnu Aryapapilaya as the information system data manager for SMP Negeri 1 Karangpucung, argues that the information system that is owned is more focused on the field of staffing where there are problems, namely IS has not been integrated with one another, causing data redundancies and hampered service processes due to SI not working effectively. If there is a problem, SMP Negeri 1 Karangpucung, especially in the field of staffing, requires planning an information system strategy using the Ward and Peppard method to produce a future information system strategy plan document by recommending future information systems that need to be retained, optimized, developed.